(untitled) (Czech Journal of International Relations, 2021)
The research looks into the authoritarian regime survival strategies in Egypt and Turkey during the COVID-19 pandemic. Furthermore, it examines how the autocratic rulers in both countries dealt with the securitization dilemma caused by the coronavirus outbreak. It applies securitization theory and the concept of selective securitization to argue that although both Abdel Fattah el-Sisi’s and Recep Tayyip Erdoğan’s rule were at some point expected to be shaken by the pandemic, the COVID-19 securitization dilemmas had an important role in helping to prolong the autocratic directions of their respective countries. Additionally, the article demonstrates that the securitization of the COVID-19 pandemic in Egypt and Turkey follows a certain political pattern where every crisis constitutes an opportunity for expanding the regimes’ powers at the expense of citizens’ rights.